A Skin‐Like and Highly Stretchable Optical Fiber Sensor with the Hybrid Coding of Wavelength–Light Intensity. (2nd December 2021) - Li, Tianliang; Su, Yifei; Chen, Fayin; Liao, Xinqin; Wu, Qin; Kang, Yan; Tan, Yuegang; Zhou, Zude
Abstract : Skin‐like electrical sensor has been widely employed for wearable human healthcare monitoring but is limited by electromagnetic interferences, poor waterproof performance, and point‐type measurement. Herein, a skin‐like and stretchable optical fiber (SSOF) sensor with excellent stretchability (up to 100%), flexibility, and excellent compliance with skin is reported. A hybrid coding based on the light intensity difference of two fiber Bragg gratings (FBGs) is created to achieve the resistance for light power fluctuations and the capability of distributed measurement. The SSOF sensor has outstanding durability (>10 000 cycles), waterproofness, and impact resistance. And it can stably work in heat (55 °C) or cold (≈0 °C) environment as well. Furthermore, the SSOF sensor‐based human–computer interaction system is created to achieve the distributed monitoring of physiological parameters and human full‐body movement leading to the enormous potential for virtual reality (VR) and rehabilitation therapy. Abstract : Herein, a skin‐like and stretchable optical fiber sensor (SSOF sensor) with the hybrid coding of wavelength‐light intensity for healthcare monitoring is introduced. It demonstrates high stretchability (up to 100%) and excellent comprehensive performance, and the ability to achieve the distributed measurement for physiological parameters and human body movement parameters.